Ethnic Variation in Central Corneal Refractive Power and Steep Cornea in Asians - Pan, Chen-Wei; Cheng, Ching-Yu; Sabanayagam, Charumathi; Chew, Merwyn; Lam, Janice; Ang, Marcus; Wong, Tien Y. (Ophthalmic epidemiology, 2014)
Abstract Purpose: To describe ethnic differences in the distribution of central corneal refractive power and steep cornea in a multiethnic Asian population. Methods: A total of 2968 Chinese, 2957 Indian and 2928 Malay participants aged over 40 years were included in this study. Each subject underwent standardized systematic and ocular examinations, interviewer-administered questionnaires, and blood investigations for risk factor assessment. Central corneal refractive power was measured using an autorefractor. Steep cornea was defined as central corneal refractive power exceeding 48 diopters (D) measured by keratometry. Results: Mean keratometry readings were 43.9 ± 1.5 D in Malays, 44.2 ± 1.5 D in Indians and 43.9 ± 1.5 D in Chinese. The prevalence of steep cornea was 0.6% (95% confidence interval, CI, 0.3-0.9%) in Malays, 1.0% (95% CI 0.7-1.4%) in Indians and 0.5% (95% CI 0.3-0.8%) in Chinese. In multivariate analysis, increasing central corneal refractive power was associated with Indian race, shorter body height, non-smokers, absence of pterygium, shorter axial length, thinner corneas and greater anterior chamber depth, while the presence of steep cornea was significantly associated with Indian race, shorter axial length and thinner corneas. Conclusions: Indian participants had the steepest corneas among the three major ethnic groups in Singapore. Central corneal refractive power was related to several ocular parameters including anterior chamber depth, axial length and central corneal thickness. These data have important clinical implications for understanding the risk of keratoconus.